Binder-scale creep behavior of metakaolin-based geopolymer. (October 2019) - Chen, Shikun; Wu, Chenglin; Yan, Dongming
Abstract: In this study, the creep behavior of binder phase in metakaolin-based geopolymers (MKGs) was investigated using nanoindentation. The underlying influence of the Si/Al ratio on the creep behavior was determined from detailed microstructure characterization and micromechanical analysis. The results indicated a strong correlation between the binder-scale creep behavior in MKG and its microstructure, particularly the characteristic pore size, which was further related to the Si/Al ratios of the binder. Combined with micromechanical analysis, the underlying influence of the composition and structure on the creep behavior in MKG was further explained. Graphical abstract: Unlabelled Image Highlights: Binder-scale indentation shows the creep/elastic behavior of metakaolin-based geopolymer (MKG) vary with its Si/Al ratio. The influences of Si/Al ratio on creep/elastic properties are attributed to the changes of pore structure of the binder. Micromechanics analysis indicates a surface layer may account for the pore-size effect in creep/elastic behavior of MKG.